Attenuated vaccinia virus-circumsporozoite protein recombinants confer protection against rodent malaria. - Lanar, D E (1996)
NYVAC-based vaccinia virus recombinants expressing the circumsporozoite protein (CSP) were evaluated in the Plasmodium berghei rodent malaria model system. Immunization of mice with a NYVAC-based CSP recombinant elicited a high level of protection (60 to 100%). Protection did not correlate with CS repeat-specific antibody responses and was abrogated by in vivo CD8+ T-cell depletion. Protection was not enhanced by modification of the subcellular localization of CSP. These results suggest the potential of poxvirus-based vectors for the development of vaccine candidates for human malaria.